Sirculer Mobility and the Sosial Economic - Astuti, Wahyuni Apri (Forum Geografi, 1996)
The different between permanent and non permanent mobility lies with the will or will not intend to settle at the destination residences. If someone move to another residences and does not intend to settle permanently then this kind of movement is called circular migration. Migrant motivation usually has economic motive, urban-migrant is bigger than rural-migrant in quantity. Rural-migrants are generally the transmigrants whose activity is in farming sector. Circular migration is much more than permanent migration. Such a thing is caused by centripetal and centrifugal force of same power. Population is faced with the problem of selection, to settle at the rural with hard economy condition or migrate to another region. To solve the problem, then, they usually decide to move to the other region performing circular mobility. Circular mobility gives a positivesÂ effect in economic condition, education, and development to the region where the migrants come from. The presence of consigment and new ideas transfered to the rural. Such a thing will bring the workers rural development.